Impact of New York prescription drug monitoring program, I-STOP, on statewide overdose morbidity - Brown, R.; Riley, M.; Ulrich, L.; Kraly, Ellen; Jenkins, P.; Krupa, N.; Gadomski, A. (Elsevier Ireland Ltd, 2017)
© 2017 Elsevier B.V. Background Prescription Drug Monitoring programs (PDMPs) are intended to reduce opioid prescribing and aberrant drug-related behavior thereby reducing morbidity and mortality due to prescription opioid overdose. Expansion of the New York (NY) State's PDMP in 2013 included the institution of the I-STOP law that mandated clinicians to consult the statewide PDMP database to review the patient's prescription history prior to prescribing opioids. Methods Trends in prescription opioid distribution, prescribing, and prescription opioid and heroin overdose morbidity in NY were analyzed using time series. A Chow test was used to test the difference in trends before and after the implementation of I-STOP. Results The results indicated that: 1) the number of opioid prescriptions appears to be declining following the implementation of the I-STOP, 2) however, supply chain data shows that the total quantity of opioids in the supply chain increased, 3) statewide trends in inpatient and emergency department visits for prescription opioid overdose increased from 2010 to the third quarter of 2013 where the slope leveled off following I-STOP, but this change in slope was not significant, 4) visits for heroin overdose started escalating in 2010 and continued to increase through the second quarter of 2016. The overall significance of these findings show a small impact of PDMPs on prescription opioid overdose morbidity in NY in the context of the increasing national trend during this time period. Conclusions Prescription opioid morbidity leveled off following the implementation of a mandated PDMP although morbidity attributable to heroin overdose continued to rise.